2011
DOI: 10.1007/s11207-011-9834-2
|View full text |Cite
|
Sign up to set email alerts
|

The Helioseismic and Magnetic Imager (HMI) Investigation for the Solar Dynamics Observatory (SDO)

Abstract: The Helioseismic and Magnetic Imager (HMI) instrument and investigation as a part of the NASA Solar Dynamics Observatory (SDO) is designed to study convection-zone dynamics and the solar dynamo, the origin and evolution of sunspots, active regions, and complexes of activity, the sources and drivers of solar magnetic activity and disturbances, links between the internal processes and dynamics of the corona and heliosphere, and precursors of solar disturbances for space-weather forecasts. A brief overview of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
1,316
0
8

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 2,098 publications
(1,368 citation statements)
references
References 43 publications
7
1,316
0
8
Order By: Relevance
“…If we follow the relation ΔR R = −3 2 Δν ν , which would correspond to an upper limit for a change in solar radius of about 50 km at maximum of Cycle 23 and of about 30 km during Cycle 24. Bush et al (2015) extracted a radius change of 4 × 10 −5 over the last four years using the observations from the Helioseismic and Magnetic Imager (HMI; Scherrer et al 2012) instrument on board the Solar Dynamics Observatory spacecraft, which is compatible with the estimate extracted from the radial mode observed by the GOLF instrument. The l = 1 dipole and l = 2 quadrupole temporal variations shown in Fig.…”
Section: Discussionmentioning
confidence: 62%
“…If we follow the relation ΔR R = −3 2 Δν ν , which would correspond to an upper limit for a change in solar radius of about 50 km at maximum of Cycle 23 and of about 30 km during Cycle 24. Bush et al (2015) extracted a radius change of 4 × 10 −5 over the last four years using the observations from the Helioseismic and Magnetic Imager (HMI; Scherrer et al 2012) instrument on board the Solar Dynamics Observatory spacecraft, which is compatible with the estimate extracted from the radial mode observed by the GOLF instrument. The l = 1 dipole and l = 2 quadrupole temporal variations shown in Fig.…”
Section: Discussionmentioning
confidence: 62%
“…All the images are corrected for the solar differential rotation. For the magnetograms, we use the data observed by the Helioseismic and Magnetic Imager (HMI, Scherrer et al 2012) on board the SDO. HMI measures the photospheric magnetic field of the Sun with a cadence of 45 s and a spatial resolution 1″.…”
Section: Instrumentation and Datamentioning
confidence: 99%
“…Because there is a possibility − even if the event has no WL enhancements from the SOT data − that WL emission may exist out of the SOT field of view, we also checked the continuum data from the Helioseismic and Magnetic Imager (HMI) [29,30] onboard the Solar Dynamics Observatory (SDO) [31]. We found that both events had WL emission observed simultaneously by both instruments.…”
Section: Event Selectionmentioning
confidence: 99%